1983
DOI: 10.1289/ehp.8353155
|View full text |Cite
|
Sign up to set email alerts
|

In vitro approaches for determining mechanisms of toxicity and carcinogenicity by asbestos in the gastrointestinal and respiratory tracts.

Abstract: Organ and cell cultures of gastrointestinal and tracheobronchial epithelium have been used to document both the interaction of asbestos with mucosal cells and the sequence of cellular events occurring after exposure of cells to fibers. The biological activity of various types of asbestos in vitro is related to surface charge, crystallization, and dimensional characteristics. These factors also influence adsorption of natural secretions and serum components to fibers, a process that ameliorates cytotoxicity. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

1988
1988
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 28 publications
0
24
0
2
Order By: Relevance
“…The chemical analyses of THS extracts from these fabrics demonstrated a significant build-up of nicotine, TSNAs, and other alkaloids. These THS extracts were not cytotoxic in the MTT cell proliferation assay (data not shown), which measures mitochondrial reductase (Mossman, 1983); however, cytotoxicity may have been greater if extraction had been done in medium containing serum, as suggested by later experiments. The more sensitive live cell imaging assay clearly demonstrated that THS inhibited cell proliferation.…”
Section: Discussionmentioning
confidence: 75%
“…The chemical analyses of THS extracts from these fabrics demonstrated a significant build-up of nicotine, TSNAs, and other alkaloids. These THS extracts were not cytotoxic in the MTT cell proliferation assay (data not shown), which measures mitochondrial reductase (Mossman, 1983); however, cytotoxicity may have been greater if extraction had been done in medium containing serum, as suggested by later experiments. The more sensitive live cell imaging assay clearly demonstrated that THS inhibited cell proliferation.…”
Section: Discussionmentioning
confidence: 75%
“…The IC 50 values of each parameter were calculated. To determine the possible toxic effects of the extract and the terpenes on the mammalian cells, uninfected macrophages were incubated at 37°C with the compounds, and cell viability was measured by the MTT colorimetric assay (Mossman 1983). The absorbance was measured at 490 nm with a spectrophotometer (VERSAmax Tunable, Molecular Devices, USA), and the LC 50 parameter, corresponding to the concentration that leads to 50% of viability loss, was measured.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of THS accumulation were assessed in the MTT assay, which measures mitochondrial reductase activity and can be used to assess cell survival and health (Figure 6). 82 Toxicity was observed in extracts taken from terry cloth exposed to the equivalent of 54 cigarettes over an 8-month period. The surface loading of THS on the terry cloth was 0.7 μ g·cm −2 .…”
Section: Progress and New Evidencementioning
confidence: 99%